2010
DOI: 10.1002/prot.22640
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale simulations of protein landscapes: Using coarse‐grained models as reference potentials to full explicit models

Abstract: Evaluating the free‐energy landscape of proteins and the corresponding functional aspects presents a major challenge for computer simulation approaches. This challenge is due to the complexity of the landscape and the enormous computer time needed for converging simulations. The use of simplified coarse‐grained (CG) folding models offers an effective way of sampling the landscape but such a treatment, however, may not give the correct description of the effect of the actual protein residues. A general way arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
102
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(109 citation statements)
references
References 44 publications
1
102
0
Order By: Relevance
“…Often referred to as constant pH MD (CPHMD) simulations, the titration coordinate is typically implemented in either a discrete manner [31][32][33][34][35][36][37][38][39][40][41][42][43] where protonation states are modified with an MC step at some regular MD interval or using a continuous function [44][45][46] that describes the protonation state via the k dynamics method developed by Brooks and coworkers. [47][48][49] Recent studies have shown that CPHMD is a reliable and robust method that is capable of predicting pK a values in a variety of biomolecular systems.…”
Section: Introductionmentioning
confidence: 99%
“…Often referred to as constant pH MD (CPHMD) simulations, the titration coordinate is typically implemented in either a discrete manner [31][32][33][34][35][36][37][38][39][40][41][42][43] where protonation states are modified with an MC step at some regular MD interval or using a continuous function [44][45][46] that describes the protonation state via the k dynamics method developed by Brooks and coworkers. [47][48][49] Recent studies have shown that CPHMD is a reliable and robust method that is capable of predicting pK a values in a variety of biomolecular systems.…”
Section: Introductionmentioning
confidence: 99%
“…18 and 20) is also unlikely to yield the correct free energy trend. Thus we used in this work our CG model that focuses on consistent description of the electrostatic energy of the system (21). We assumed that because this CG model has been very effective in reproducing protein folding energies and other properties (22,23), it should provide an effective strategy for capturing the energetics underlying the function of molecular motors.…”
mentioning
confidence: 99%
“…We have embedded the system in a rectangular membrane where both the protein and the lipid were represented by our CG model. The protein residues were represented with explicit backbone atoms and the side chains were represented with a single united atom (21), while the membrane was represented through a grid of effective atoms with a 3 Å spacing. The membrane block has a width of about 30 Å and the central Asp residues of the c-ring were placed almost at the middle of the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to emphasize that previous attempts to model the asymmetry were not based on a validated experience in modeling charges in protein interiors or on familiarity with the corresponding issue. This is exactly the issue that has been extensively studied by us (26) and has led to the electrostatic features of our CG model (21). At present, the CG is far more reliable in assessing pK a and electrostatic free energies in nonpolar regions of protein/membrane systems than the standard FEP calculations [e.g., of the type used in ref.…”
mentioning
confidence: 85%
See 1 more Smart Citation